SI Desa (Sistem Informasi Desa): Initiation of an Integrated Village Economic Information System and Data Management by the Provincial Government of East Java (Jurnal Bina Praja, 2023)
Implementing regional autonomy gives local governments the authority to provide freedom in regulating and managing their area. Rural development is an essential part of supporting the success of regional development. However, problems were found in the information system and management of village economic data, which resulted in slow village government work processes in collecting information system data and the difficulty for the community to obtain information about the village economy. This study aims to analyze the East Java Provincial Government in initiating the SI Desa Service as a form of providing information system services and computer-based village data management and an integrated website that is easy to access for users. This qualitative research uses an analytical tool as a business model canvas with secondary data because it can develop SI Desa Services through its nine components. The research results by the Provincial Government of East Java through the Community and Village Empowerment Office, which collaborated through a memorandum of understanding with other stakeholders involved in initiating an ideal information system for village economic data management in the SI Desa Service. This integrated service will become a village economic information system and data management that is transparent, accountable, and right on target and can be monitored for its usefulness. The village government can provide excellent service so that all villages integrated with this service can become more resilient and self-sufficient.
Keywords: business model canvas; village data management; village information system; regional autonomy